LIQUIDITY RISK DISCLOSURE: A REVIEW OF CORPORATE GOVERNANCE - Shinta Permata Sari; Himmatus Sholikhah (Riset Akuntansi dan Keuangan Indonesia, 2019)
Liquidity risk is the potential loss arising from the inability of a company to fulfill its obligations or to fund an increase in assets at maturity without incurring unacceptable costs or losses. The purpose of this study is to analyze the corporate governance factors that influence liquidity risk disclosure. Its factors are the proportion of independent commissioners, audit committees, managerial ownership, and institutional ownership. The sampling technique used a purposive sampling method in consumer goods industrial classification companies listed on the Indonesia Stock Exchange on 2016-2018. The multiple regression uses to analyze the data. Results indicate that the proportion of commissioners and audit committees have an effect on liquidity risk disclosure, meanwhile managerial ownership and institutional ownership have no effect on liquidity risk disclosure.Keywords: liquidity risk disclosure, the proportion of independent commissioners, audit committees, managerial ownership, institutional ownership.